2021
DOI: 10.1002/pon.5694
|View full text |Cite
|
Sign up to set email alerts
|

Variables associated with distress amongst informal caregivers of people with lung cancer: A systematic review of the literature

Abstract: Objective Informal caregivers of people with lung cancer often experience a substantial care burden and associated negative consequences due to the often‐contracted course of the disease. The objective of this review was to systematically examine the evidence on the factors associated with lung cancer caregiver distress. Methods Five databases (MEDLINE, CINAHL, EMBASE, PsychINFO and Web of Science) were searched for studies investigating factors associated with distress amongst caregivers of people with lung c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 64 publications
1
24
0
1
Order By: Relevance
“…Other treatment variables, which were expected to be significantly associated with caregiving awareness, as noted in Cochrane et al’s systematic review [ 49 ], were found to be statistically significant in the bivariate analysis but not in the multivariate analysis. These include the degree of religiosity and financial status, along with the number of treatment days per week and involvement in patient care activities.…”
Section: Discussionmentioning
confidence: 98%
“…Other treatment variables, which were expected to be significantly associated with caregiving awareness, as noted in Cochrane et al’s systematic review [ 49 ], were found to be statistically significant in the bivariate analysis but not in the multivariate analysis. These include the degree of religiosity and financial status, along with the number of treatment days per week and involvement in patient care activities.…”
Section: Discussionmentioning
confidence: 98%
“…Caregivers may have more positive memories if they perceive that what they have done has fulfilled the wishes of the patient, despite the experience of emotional difficulties during the end-of-life transition [ 55 , 56 ]. Although most caregivers will gradually return to normal life after the death of the patient, some may experience severe post-loss distress, which can result in higher levels of anxiety and depression [ 58 60 ]. Parents of children who have died of cancer are likely to experience post-loss distress and prolonged grief symptoms due to regret and unfinished business [ 61 ].…”
Section: Impact Of Caregiving On Informal Cancer Caregiversmentioning
confidence: 99%
“…Other identified intrapersonal factors are the coping strategies, self-efficacy, and resilience of caregivers [ 60 , 71 ]. Maladaptive coping by caregivers is associated with a poorer health profile in cancer survivorship and end-of-life care [ 68 , 72 ] and prolonged grief symptoms in bereavement [ 72 , 73 ].…”
Section: Factors Influencing Informal Cancer Caregivingmentioning
confidence: 99%
See 1 more Smart Citation
“…Nesse ponto de vista, outro fator importante é que os enfermeiros que trabalham nos cenários oncológicos experimentam intenso estresse emocional devido às recorrentes perdas, terapêuticas prolongadas e complexas, pacientes com níveis álgicos elevados, entre outras situações estressoras. Quanto ao manejo das múltiplas emoções, esses profissionais gerenciam não só as dos pacientes, bem como as suas também Carmo et al, 2019;Cochrane et al, 2021) Devido ao papel crítico dos enfermeiros oncológicos no atendimento aos pacientes, entender os fatores que influenciam sua satisfação e desempenho no ambiente de trabalho tem implicações importantes para a prática clínica. A satisfação no trabalho entre eles é um fenômeno variável e complexo que depende de inúmeros fatores, como, equipamentos adequados, segurança e remuneração no emprego, oportunidades de desenvolvimento, apoio do supervisor, autonomia, qualidade das relações no ambiente laboral e a sensação de que o trabalho faz a diferença (Kitajima et al, 2020).…”
Section: Nos Estudos Desenvolvidos Porunclassified